RANCANG BANGUN WIRELESS POWER TRANSFER (WPT) MENGGUNAKAN METODE MULTI - MAGNETIC RESONATOR COUPLING - Toto Supriyanto; Asri Wulandari (Politeknik Negeri Jakarta, 2015)
Abstract Magnetically coupled coils have been widely used for a variety of applications requiring contactless or wireless power transfer (WPT). In this paper, the wireless power transfer (WPT) using Copper (Cu) and Aluminium (Al) as magnetic coupling is designed, fabricated and measured. A main problem of wireless power transfer (WPT) is about low efficiency. As state of the art, this research will investigate the effects of the use of copper and aluminum as magnetic coupling. A Copper (Cu) and Aluminium (Al) are used as transmitter (Tx) and receiver (Rx) vice versa. A power analysis has been carried out to identify the efficiency system. The measurement result shown that the wireless power transfer (WPT) using aluminum as transmitter (Tx) and receiver (Rx) have the highest efficiency. The overall efficiency of the power being transferred is about 7,51%-10,8% at distance 20 cm. This research shown that aluminum can consider as a material for the wireless power transfer with magnetic induction method. Keywords: wireless power transfer, receiver, transmitter, copper, aluminium Abstrak Magnetically coupled coils digunakan untuk bermacam-macam kebutuhan pemakaian tanpa kontak langsung atau transfer daya tanpa kabel ( WPT). Pada paper ini, transfer daya tanpa kabel (WPT) menggunakan tembaga dan aluminium sebagai magnetic coupling yang di rancang, pabrikasi dan diukur. Permasalahan utama dari WPT adalah efisiensi daya rendah. Sebagai state of the art, penelitian ini akan membahas pengaruh dari penggunaan tembaga dan aluminium sebagai magnetic coupling. Sebuah tembaga dan aluminium digunakan sebagai pemancar (TX) dan penerima (Rx). Analisis daya dilakukan untuk melihat efisiensi system. Hasil pengukuran didapatkan bahwa WPT menggunakan aluminium sebagai pemancar dan penerima mempunyai efisiensi tertinggi. Efisiensi daya yang di transfer sekitar 7,51%-10,8% pada jarak 20 cm. Hal tersebut membuktikan bahwa bahan aluminium layak dipertimbangkan dalam penggunaannya sebagai material penyusun antena dalam alat transfer daya tanpa kabel dengan metode induksi resonansi magnetik Katakunci : WPT, Ring Loop, Antena, Tembaga, Alumunium